Affirmative Computing in Health Science : Towards Inclusive and Empathetic Digital Health Systems (International Journal of Scientific Research in Science and Technology, 2025)
Affirmative computing is an emerging interdisciplinary paradigm that focuses on embedding values of empathy, inclusivity, and positive reinforcement into digital systems. In the realm of health sciences, where the interplay between technology and human well-being is critical, affirmative computing offers a transformative approach. This paper explores the philosophical and theoretical underpinnings of affirmative computing, its technological implementation, diverse applications in healthcare domains, ethical considerations, and future research directions. Through an in-depth analysis of existing literature, case studies, and practical examples, we aim to elucidate how affirmative computing can create emotionally intelligent, inclusive, and patient-centric healthcare technologies.